2013
DOI: 10.3390/rs5020864
|View full text |Cite
|
Sign up to set email alerts
|

Use of Satellite Radar Bistatic Measurements for Crop Monitoring: A Simulation Study on Corn Fields

Abstract: This paper presents a theoretical study of microwave remote sensing of vegetated surfaces. The purpose of this study is to find out if satellite bistatic radar systems can provide a performance, in terms of sensitivity to vegetation geophysical parameters, equal to or greater than the performance of monostatic systems. Up to now, no suitable bistatic data collected over land surfaces are available from satellite, so that the electromagnetic model developed at Tor Vergata University has been used to perform sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Several theoretical studies have shown that the elevation angle has an influence on the bistatic signal penetration down to the soil and the retrieval of vegetation parameters [33,34]. For this reason, our statistical analysis of the GNSS-R measurements makes use of two elevation intervals (50-70 • and 70-90 • ).…”
Section: Discussionmentioning
confidence: 99%
“…Several theoretical studies have shown that the elevation angle has an influence on the bistatic signal penetration down to the soil and the retrieval of vegetation parameters [33,34]. For this reason, our statistical analysis of the GNSS-R measurements makes use of two elevation intervals (50-70 • and 70-90 • ).…”
Section: Discussionmentioning
confidence: 99%
“…Intensification, on the other hand, achieves higher yields through increased inputs, improved agronomic practices (e.g., drop irrigation), improved crop varieties and other innovations. Papers [30][31][32][33] demonstrate how remote sensing can contribute to the mapping of land under agricultural production. The review paper of Rembold et al (this issue) [34] provides an overview of remote sensing techniques for yield mapping.…”
Section: Environmental Impacts Of Agriculture and Future Pathways Formentioning
confidence: 99%
“…Besides these problems, Foody (2010) [135] points out the importance of ground truthing. The papers [33,[35][36][37] of this special issue provide examples on how to use remote sensing data for reconstructing past land use patterns at the landscape level.…”
Section: Disturbances and Land Use/land Cover Changesmentioning
confidence: 99%
“…Scattering from soil is often a dominant element in the return from vegetated surfaces, and owing to the uncertainties in moisture and roughness it remains a challenging problem to model surface contributions from backscattering alone. Guerriero et al [7] report simulations for corn fields in which the potential for obtaining crop parameters is claimed. Carreno-Luego et al [8] have presented measurements of scattering of GNSS-R signals received bistatically and multistatically from a stratospheric platform over boreal forests which showed that there are important polarimetric signatures involving the canopy-soil interaction.…”
Section: Introductionmentioning
confidence: 99%